Materials for a Theory of the Duration of the Process of Tax Shifting - Fasiani, Mauro (Review of Economic Studies, 1935)
Journal Article Materials for a Theory of the Duration of the Process of Tax Shifting Get access Mauro Fasiani Mauro Fasiani Genoa Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 2, February 1935, Pages 122–136, https://doi.org/10.2307/2967559 Published: 01 February 1935